Spectrum of Tuberculosis in BCG Vaccinated and Unvaccinated Children - Najaf Masood , Mudassir Sharif, Rai Asghar (Journal of Rawalpindi Medical College, 2010)
Background: To study the clinical spectrum of tuberculosis in BCG vaccinated and unvaccinated children. Method: In this descriptive study patients aged 0-15 years who presented with signs and symptoms suggestive of tuberculosis were included. BCG scar was taken as sole indicator of BCG vaccination. All the data was subjected to Pakistan Paediatric Association Scoring Chart for diagnosis of TB in children and recorded on a proforma. Score seven or more indicated confirmed Tuberculosis (TB). Results: Total of 108 patients showed score more than seven. More than half (57.4%) patients were BCG vaccinated. Close contact with TB patients was found in 76 (70.4%) patients. Strongly suggestive physical findings were present in 46 (42.6%) while suggestive radiological findings were appreciated in 76(70.4%) patients. Mantoux test was positive (induration more than 10 mm) in 37(34.3%) patients. Pulmonary TB was present in 62(55.6%), tuberculous meningitis (TBM) in 27(25%), tuberculous lymphadenitis in 10(9.3%) and miliary TB . in 6(5.6%). Conclusion: No statistical significance was found in pulmonary and extra pulmonary TB among vaccinated and unvaccinated children. Younger children were found to be more affected by their close contacts inspite of being vaccinated.